AASHTO LRFD bridge construction specifications : 4th edition (American Association of State Highway and Transportation Officials, 2017)
The AASHTO LRFD Bridge Construction Specifications are intended for use in the construction of bridges. The specifications employ the Load and Resistance Factor Design (LRFD) methodology, and are designed to be used in conjunction with the AASHTO LRFD Bridge Design Specifications. Revisions from the 3rd edition of this title include a complete revision of Section 3, Temporary Works, and changes to Section 10, Prestressing; Section 11, Steel Structures; Section 19, Bridge Deck Joint Seals; and Section 27, Concrete Culverts.
"Publication code: LRFDCONS-4"--T.p. verso
Keywords: Bridges -- Design and construction -- Specifications -- United States.; Bridges -- Maintenance and repair -- Specifications -- United States.; Bridges -- Live loads -- Specifications -- United States.; elektronické knihy; electronic books